Scalp-Ear-Nipple Syndrome: A Case Report - Estela Morales-Peralta; Vivian Andrés; Dainé Campillo Betancourt (Case Reports in Medicine)
The scalp-ear-nipple (SEN) syndrome is an infrequent congenital disease. Its main features are scalp defects, malformed ears, and absence of nipples. Most of the reported cases are autosomal dominant. We report on a patient suffering SEN syndrome with possible autosomal recessive inheritance. It is concluded that SEN syndrome should be recognized as an entity with genetic heterogeneity once there is evidence of different genetic manner of inheritance described in this disease.